The polymorphism of ANXA9 gene and its relationship with body dimensions in Awassi Sheep (Indian Journal of Animal Production and Management, 2025)
This study was conducted at the sheep and goat breeding station in Shatrah city, Thi  Qar Governorate, southern Iraq, and included 39 Awassi ewes aged 2-4 years. The  aim of the research was to study the effect of the polymorphism of the ANXA9 gene  on some body dimension traits in Awassi sheep to benefit from it in early selection  for these traits. Blood samples were collected from the jugular vein of each animal,  and then the genetic material (DNA) was extracted from them. Then, the targeted  segment of the studied gene was amplified using PCR technology and electrophoresis  was performed to confirm the size of the targeted segment of the gene in the Molecular  Genetics Laboratory of Thi Qar University. The results showed the presence of three  variations (SNPs) in the targeted segment (172 C/G, , 385 G/T,393G/C) occurred in  intron 4 of chromosome 1in sheep. The three SNPs did not differ significantly between  their genotypes according to the resulting Chi-square value. The first mutation (GC)  had no significant effect on the studied body dimensions, while the GT mutation  showed a significant effect on the body length, chest and abdominal circumference  traits in sheep. There was also a significant difference for the CG mutation in the  front and rear height traits of sheep, which indicates the possibility of using them as  selective indicators for these traits in Awassi sheep.
Keywords: ANXA9 gene; SNPs; Body dimensions; Awassi sheep